Body mass index and serum levels of soluble leptin receptor are sex-specifically related to alcohol binge drinking behavior - Bouna-Pyrrou, Polyxeni; Mühle, Christiane; Kornhuber, Johannes; Weinland, Christian; Lenz, Bernd (Psychoneuroendocrinology, 2021)
Objective: Binge drinking is a highly prevalent behavior in adolescents and young adults and a risk factor to develop alcohol use disorder. Body mass index (BMI) and blood levels of leptin peptide and its soluble receptor have been implicated in alcohol use disorder; however, their role in binge drinking remains to be investigated. Method: We studied associations of BMI, serum levels of soluble leptin receptor (ObRe) and leptin as well as the free leptin index with binge drinking in 93 male and 99 female young adults. Results: In men, binge drinkers showed significantly higher BMI (kg/m2) than non-binge drinkers (23.67 vs. 22.08) and higher BMI correlated significantly with more severe binge drinking episodes (ρ = 0.251). In women, we found significantly higher ObRe (ng/ml) / BMI (kg/m2) values in binge drinkers than in non-binge drinkers (0.52 vs. 0.44) and ObRe/BMI values correlated significantly with more severe binge drinking episodes (ρ = 0.210). Conclusion: This study confirms that higher BMI associates with binge drinking in men and shows for the first time a role of ObRe/BMI in binge drinking in women. Our data emphasize the importance of further research in the ﬁeld of metabolic markers and implications in neurobiological processes of binge drinking.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Alcohol binge drinking; Body mass index; Leptin; Soluble leptin receptor

Cross-Sectional and Longitudinal Evaluation of the Social Network Use Disorder and Internet Gaming Disorder Criteria - Bouna-Pyrrou, Polyxeni; Aufleger, Birte; Braun, Simona; Gattnar, Manja; Kallmayer, Sofia; Wagner, Helena; Kornhuber, Johannes; Mühle, Christiane; Lenz, Bernd (Frontiers in Psychiatry, 2018)
Background: The inclusion of internet gaming disorder (IGD) as a condition warranting more research in the DSM-5 has led to a rapid increase of research on addictive internet activities. Further evaluation of the criteria for IGD and social network disorder (SND) is needed. Objective: To assess the internal consistency, construct validity, retest-reliability, and long-term stability of SND and IGD criteria in German-speaking cohorts. Method: We conducted total and sex-specific analyses on data from two cross-sectional and longitudinal studies, one sample of 192 participants enriched for internet use and another community-based sample of 2316 individuals. Results: First, independent from assessment setting (online, telephone, on-site) and gender, we found acceptable to good internal consistency for SND and IGD criteria (Cronbach's α 0.690-0.774 for SND and 0.743-0.866 for IGD, respectively). Second, positive Spearman correlations between the sum of affirmed criteria and established scales of pathological internet use (ρ 0.395-0.783) and time spent on the social networking sites or internet gaming (ρ 0.317-0.761) confirmed convergent validity. Moreover, the sum of affirmed criteria related positively to attentional impulsivity (ρmax 0.311), urgency (ρ 0.124-0.200), and neuroticism (ρmax 0.210), and negatively to perseverance (ρ -0.245- -0.098) and conscientiousness (ρmin -0.257). Finally, SND and IGD criteria showed high retest stability (SND ρ 0.653-0.826, IGD ρ 0.714-0.825, respectively). However, participants scored higher on SND and IGD scales during the online compared to the on-site assessment. The 2-year follow-up revealed an increase in affirmed SND and IGD criteria. Conclusion: Our data support good psychometric properties of the SND and IGD criteria and outline the addictive potential of social networking sites.
EVALuna2:211611

Digit ratio (2D:4D) and academic success as measured by achievement in the academic degree "Habilitation" - Tektas, Ozan Yueksel; Kapsner, Lorenz; Lemmer, Miriam; Bouna-Pyrrou, Polyxeni; Lewczuk, Piotr; Lenz, Bernd; Kornhuber, Johannes (PLoS ONE, 2019)
Introduction
CRIS-Team WoS Importer:2019-03-15

Digit ratio (2D:4D) and behavioral symptoms in primary-school aged boys - Eichler, Anna; Heinrich, Hartmut; Moll, Gunther; Beckmann, Matthias; Goecke, Tamme W.; Fasching, Peter; Muschler, Marcel-Rene; Bouna-Pyrrou, Polyxeni; Lenz, Bernd; Kornhuber, Johannes (Early Human Development, 2018)
The second-to-forth digit length ratio (2D:4D) is considered to be a biomarker for intrauterine androgen levels. It is associated with adult and child mental health problems, primarily with behavioral symptoms and predominantly in males. Using a cross-sectional design, we examined whether 2D:4D was associated with conduct disorder (CD) symptoms in 138 primary-school aged children (54% boys, Mage = 7.70 years) and considered child sex as a moderating factor. Children's digit lengths were measured from hand scans and mothers rated the behavioral/emotional symptoms of their child. The regression analyses revealed that 2D:4D ratios were associated with behavioral symptoms in boys (β = -0.260, p = 0.026), but not in girls (β = -0.040, p = 0.762). Child emotional symptoms, analyzed as a control, were not significantly correlated with 2D:4D. In conclusion, prenatal brain hyperandrogenization - operationalized by the 2D:4D biomarker - could result in behavioral symptoms in boys at early school age, reflecting one predictor for early onset CD. Our data support the use of 2D:4D as a marker of prenatal androgen exposure.
EVALuna2:36369

Digit ratio (2D:4D) in relation to substance and computer use: a meta-analysis - Siegmann, Eva-Maria; Bouna-Pyrrou, Polyxeni; Lenz, Bernd; Kornhuber, Johannes (Journal of Neural Transmission, 2019)
Human studies have reported inconsistent associations between the length ratio of the second finger to the fourth finger (2D:4D), which is a proxy for prenatal androgen load, and substance or computer use in adolescents and adults. This meta-analysis quantifies the magnitude of this relationship and investigates the roles of sex, definition of caseness, different forms of addiction, the hand measured (right hand versus left hand), and other cohort characteristics. Univariate random-effects meta-analyses were performed, and moderators were tested with Bonferroni-corrected meta-regression analyses. The study included 18 independent samples with a total of 175,955 participants (96,316 males and 79,639 females). There was a significant difference in 2D:4D between the substance and computer-using subjects and the controls for the combined sample (Hedge’s g = − 0.178 [− 0.291; − 0.064]) and for males (Hedge’s g = − 0.260 [− 0.399; − 0.122]), but not for females. These effects were amplified when only analyzing studies that compared dependent versus non-dependent subjects (combined sample: g = − 0.325 [− 0.492; − 0.157]; males: g = − 0.427 [− 0.564; − 0.291]), but did not reach significance in the subgroup of studies examining other parameters of substance and computer use. When analyzing different forms of substance and computer use separately, alcohol intake and computer use revealed a significant difference in the standardized mean. Again, the effects were amplified when analyzing the subgroup of males and the subgroup of studies comparing dependent versus non-dependent subjects, with effect sizes showing Hedge’s g values as many as − 0.552 [− 0.785; − 0.319] (alcohol-dependent males). Thus, this meta-analysis confirms that lower 2D:4D is associated with substance and computer dependency. Further studies are encouraged to explore the link between intrauterine hormone environment and addiction risk.
CRIS-Team Scopus Importer:2019-05-14
Keywords: 2D:4D; Alcohol; Androgens; Brain organization; Prenatal androgen exposure; Substance use; Testosterone; Tobacco

Evaluation of the German biographic screening interview for fetal alcohol spectrum disorder (BSI-FASD) - Widder, Michael; Mierzwa, Luisa; Schwerg, Lina; Schecke, Henrike; Kornhuber, Johannes; Bouna-Pyrrou, Polyxeni; Bumb, Jan Malte; Richter-Schmidinger, Tanja; Lenz, Bernd (Scientific Reports, 2021)
Alcohol consumption during pregnancy may lead to permanent damage in the offspring, including fetal alcohol spectrum disorders (FASD), which have an estimated prevalence of 1–8% worldwide. In adulthood, diagnosing FASD is time-consuming and costly. This study aimed to evaluate the discriminatory power of a German screening instrument for FASD in adults—the biographic screening interview (BSI-FASD). In an open-label comparative cohort study wherein a one-time survey was administered per participant, we compared 22 subjects with confirmed FASD with control groups of 15 subjects diagnosed with attention deficit hyperactivity disorder (ADHD), 20 subjects with alcohol or opiate dependence, 18 subjects with depression, and 31 controls without prenatal alcohol exposure. The BSI-FASD was found to be resource-efficient, user-friendly, comprehensible, and easily applicable. It provided an overall good convergent and discriminant validity with a sensitivity of 0.77 (adapted 0.86) and specificities between 0.70 and 1.00. The BSI-FASD subdomains differed in their power to differentiate FASD from the groups. This study established that the BSI-FASD is an efficient instrument to screen adults with suspected FASD. The BSI-FASD may facilitate future diagnostic evaluation and thereby contribute to improved treatment of affected individuals.
CRIS-Team Scopus Importer:2021-03-19

Internet gaming disorder, social network disorder and laterality: handedness relates to pathological use of social networks - Bouna-Pyrrou, Polyxeni; Mühle, Christiane; Kornhuber, Johannes; Lenz, Bernd (Journal of Neural Transmission, 2015)
The internet age bears new challenges that include health risks. It is agreed that excessive internet use may reach pathological levels. However, the concept of internet addiction lacks specificity and, therefore, warrants studies on its diagnostic and etiologic classification. This study was conducted to characterize the novel DSM-5 criteria for internet gaming disorder and the adapted criteria for the "social network disorder". Based on the established association of handedness and substance use disorders, we also explored whether internet use related to laterality. For this study, 3,287 volunteers participated in the online survey and gave particulars concerning their internet use in general, internet gaming and use of social networks, laterality markers (hand, foot, eye, ear, rotational preference in gymnastics, and head turning asymmetry) and health status. Of the participants, 1.1 % fulfilled the criteria for internet gaming disorder, and 1.8 % fulfilled the criteria for social network disorder. The applied criteria were highly correlated with the time spent on the respective internet activities (p < 4 × 10(-56)). The analyses of comorbidity and working hours support the thresholds of 5/9 criteria and >=30 h/week spent on the internet for the classification as pathological (p < 5 × 10(-2)). Moreover, we found that left-handedness related to more affirmed criteria and longer times spent on social networks (p <= 4 × 10(-2)). The provided criteria proved to be user-friendly, comprehensible and well accepted. The results contribute to a better understanding of pathological internet gaming and social network use and provide evidence that biological markers of substance use disorders are involved in internet addiction.
EVALuna2:23695

Low digit ratio (2D:4D) and late pubertal onset indicate prenatal hyperandrogenziation in alcohol binge drinking - Lenz, Bernd; Bouna-Pyrrou, Polyxeni; Mühle, Christiane; Kornhuber, Johannes (Progress in Neuro-Psychopharmacology & Biological Psychiatry, 2018)
BACKGROUND: Alcohol binge drinking behavior is an important public health issue. Causal rodent and human associational studies show that reinforcement of prenatal androgen signaling increases alcohol consumption in adulthood. However, the effects of prenatal androgen exposure on adult binge drinking patterns have not been investigated yet. METHOD: We analyzed data from 2225 participants of an online survey (conducted 06-07/2016) to evaluate biomarkers for prenatal androgen exposure (second-to-fourth finger length ratio [2D:4D], age at spermarche or menarche as hallmark for pubertal onset) in binge drinking (≥1 episode of 15+, 10+, and/or 5+ standard drinks of 13 g of alcohol within 2 h during the 24 month- and 2 week-recall periods). RESULTS: Men reported binge drinking more often than women (ORs > 1.4, P < .001). For the 24 month-recall period, binge drinkers showed lower 2D:4D (P = .006) and reported later pubertal onset (P = .022) than non-binge drinkers. These findings consistently suggest excess prenatal androgen exposure in adult binge drinkers. Moreover, 2D:4D was negatively associated with severity (15+/10+/5+/non-binge drinking, P = .005) and frequency of binge drinking episodes (P = .044). All of these effects were stronger in men than in women. For the 2 week-recall period, the biomarkers were not significantly related to binge drinking behavior. CONCLUSION: Our results indicate that increased prenatal androgen exposure is involved in the development of alcohol binge drinking behavior in adults.
EVALuna2:211636

Low digit ratio (2D:4D) in male suicide victims - Lenz, Bernd; Thiem, Daniela; Bouna-Pyrrou, Polyxeni; Mühle, Christiane; Stoessel, Christina; Betz, Peter; Kornhuber, Johannes (Journal of Neural Transmission, 2016)
Although women attempt suicides equally or more often than men do, men are more likely to die of suicide than women (sex paradox of suicidal behavior). Furthermore, the male traits of aggression and impulsivity predict suicide completion. Here, we studied the second-to-fourth-finger length ratio (2D:4D), a proxy for prenatal androgen exposure, in 46 suicide corpses and 25 non-suicide corpses. We report significantly lower 2D:4D in male suicide corpses than non-suicide corpses (p = .030, partial ? (2) = .147). There was no significant association between 2D:4D and the suicide method. Our findings indicate increased risk of suicide following higher prenatal androgen exposure in males. The results may improve future efforts to predict and prevent suicides.
EVALuna2:9427

Prenatal and adult androgen activities in alcohol dependence - Lenz, Bernd; Mühle, Christiane; Braun, B.; Weinland, C.; Bouna-Pyrrou, Polyxeni; Behrens, Juliane; Kubis, S.; Mikolaiczik, Katrin; Muschler, M. -R.; Saigali, Sarah; Sibach, M.; Tanovska, P.; et al. (Acta Psychiatrica Scandinavica, 2017)
OBJECTIVE: Alcohol dependence is more prevalent in men than in women. The evidence for how prenatal and adult androgens influence alcohol dependence is limited. We investigated the effects of prenatal and adult androgen activity on alcohol dependence. Moreover, we studied how the behaviours of pregnant women affect their children's prenatal androgen load. METHOD: We quantified prenatal androgen markers (e.g., second-to-fourth finger length ratio [2D : 4D]) and blood androgens in 200 early-abstinent alcohol-dependent in-patients and 240 controls (2013-2015, including a 12-month follow-up). We also surveyed 134 women during pregnancy (2005-2007) and measured the 2D : 4D of their children (2013-2016). RESULTS: The prenatal androgen loads were higher in the male alcohol-dependent patients compared to the controls (lower 2D : 4D, P = 0.004) and correlated positively with the patients' liver transaminase activities (P < 0.001) and alcohol withdrawal severity (P = 0.019). Higher prenatal androgen loads and increasing androgen levels during withdrawal predicted earlier and more frequent 12-month hospital readmission in alcohol-dependent patients (P < 0.005). Moreover, stress levels (P = 0.002), alcohol (P = 0.010) and tobacco consumption (P = 0.017), and lifetime stressors (P = 0.019) of women during pregnancy related positively to their children's prenatal androgen loads (lower 2D : 4D). CONCLUSION: Androgen activities in alcohol-dependent patients and behaviours of pregnant women represent novel preventive and therapeutic targets of alcohol dependence.
EVALuna2:33408

The androgen model of suicide completion - Lenz, Bernd; Röther, Mareike; Bouna-Pyrrou, Polyxeni; Mühle, Christiane; Tektas, Ozan Y.; Kornhuber, Johannes (Progress in Neurobiology, 2019)
Suicide is a devastating public health issue that imposes severe psychological, social, and economic burdens not only for the individuals but also for their relatives, friends, clinicians, and the general public. Among the different suicidal behaviors, suicide completion is the worst and the most relevant outcome. The knowledge of biological etiopathological mechanisms involved in suicide completion is limited. Hitherto, no objective markers, either alone or in combination, can reliably predict who will complete a suicide. However, such parameters are strongly needed to establish and optimize prediction and prevention. We introduce here a novel ideation-to-completion framework in suicide research and discuss the problems of studies aiming at identifying and validating clinically useful markers. The male gender is a specific risk factor for suicide, which suggests that androgen effects are implicated in the transition from suicidal ideation to suicide completion. We present multiple lines of direct and indirect evidence showing that both an increased prenatal androgen load (with subsequent permanent neuroadaptations) and increased adult androgen activity are involved in suicide completion. We also review data arguing that modifiable maternal behavioral traits during pregnancy contribute to the offspring's prenatal androgen load and increase the risk for suicide completion later in life. We conclude that in utero androgen exposure and adult androgen levels facilitate suicide completion in an synergistic manner. The androgen model of suicide completion provides the basis for the development of novel predictive and preventive strategies in the future.
EVALuna2:211632